A Meta-Analysis of Electric Cigarette Use and Lung Health Implications - Florensia, Rika; Fauzar; Roza Kurniati (HM Publisher, 2024)
Background: The global rise in electric cigarette (e-cigarette) use has prompted urgent investigation into their health effects. This meta-analysis aims to consolidate evidence regarding the impact of e-cigarette use on lung health. Methods: A systematic search of PubMed, Embase, and Cochrane Library databases was conducted, identifying studies published between 2018 and 2024 that assessed lung function, respiratory symptoms, and lung disease incidence in e-cigarette users. Studies meeting inclusion criteria were subjected to quality assessment and data extraction. Random-effects models were used for pooled analysis, and heterogeneity was assessed. Results: Twenty-three studies, encompassing 12,456 participants, were included. E-cigarette use was associated with a small but significant decrease in forced expiratory volume in 1 second (FEV1) (standardized mean difference [SMD] -0.18, 95% CI -0.26 to -0.10, p<0.001). Increased odds of wheezing (odds ratio [OR] 1.38, 95% CI 1.15 to 1.65, p=0.001) and chronic cough (OR 1.25, 95% CI 1.08 to 1.44, p=0.003) were also observed in e-cigarette users. No significant association was found with chronic obstructive pulmonary disease (COPD) incidence. Conclusion: E-cigarette use appears detrimental to lung function and associated with respiratory symptoms. Further long-term research is imperative to establish definitive conclusions on the risk of COPD and other lung diseases.